REVIEW STUDY ON THE ACADEMIC ACHIEVEMENT IN RELATION TO EMOTIONAL INTELLIGENCE AND PERSONALITY OF TEACHER TRAINEES - Lader, Seema; Patil, Harsha (International Journal of Psychosocial Rehabilitation, 2020)
Without a doubt, the goal of all education is to achieve human greatness and perfection, not just in any sphere of knowledge or activity, but in all aspects of life. The education delivered at various levels of education in the country has a significant impact on the development of children. A country's industrial progress is formed by education in a classroom, much as a skyscraper rests on the plinth. Without a solid educational foundation, a civilization cannot break free from stagnation and famine. Performance was previously assumed to be the result of a set of skills known as intelligence. Students that are emotionally disturbed perform poorly in their families, schools, and communities.